2011
DOI: 10.1002/cjoc.201190163
|View full text |Cite
|
Sign up to set email alerts
|

Unfolding of Bovine Heart Cytochrome c Induced by Urea and Guanidine Hydrochloride

Abstract: The unfolding of bovine heart cytochrome c induced by urea and guanidine hydrochloride was studied through their intrinsic fluorescence emission spectra, fluorescence phase diagrams, fluorescence quenching, size-exclusion chromatographies, native polyacrylamide gel electrophoreses and deactivation profiles. The results showed that during their unfolding in urea and guanidine hydrochloride solutions, bovine heart cytochrome c molecules existed only in a unimolecular form and their bi-molecular and/or poly-molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…As shown in our previous work, the unfolding of the bovine heart cytochrome c induced by both guanidine hydrochloride and urea is a typical two-state process [34]. Besides, in our previous work, the structure changes of bovine heart cytochrome c during the two unfolding processes were also studied.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…As shown in our previous work, the unfolding of the bovine heart cytochrome c induced by both guanidine hydrochloride and urea is a typical two-state process [34]. Besides, in our previous work, the structure changes of bovine heart cytochrome c during the two unfolding processes were also studied.…”
Section: Resultsmentioning
confidence: 82%
“…In previous work, we determined the intrinsic fluorescence emission spectrum, fluorescence phase diagram, and fluorescence quenching and deactivation profile for the unfolding of bovine heart cytochrome c induced by urea and guanidine hydrochloride and found that the unfolding of bovine heart cytochrome c induced by both guanidine hydrochloride and urea was a typical two-state process [34] .…”
Section: Methodsmentioning
confidence: 99%